Changing livelihoods in rural Cambodia: Evidence from panel household data in Stung Treng - Rasadhika Sharma; Thanh Tung Nguyen; Ulrike Grote; Trung Thanh Nguyen (University of Bonn, Center for Development Research (ZEF), 2016)
Analysis of livelihood strategies can aid to understand and resolve problems associated with vulnerability to poverty and food security. This paper aims to identify and describe the changes in rural livelihood activities by using household data for 2013 and 2014 collected in Stung Treng, Cambodia. We use the same variables and estimate different clusters for both the years. The paper concludes that despite the lag of only one year, there are noticeable changes in livelihood strategies. Firstly, we find a group of transition farmers in 2014 that is composed of households that are witnessing a shift towards commercialization. They invest and consume more than subsistence farmers. Secondly, there is a greater diversification in activities amongst the groups. Most households practice multiple activities. Lastly, with regards to self-employment, there has been a shift from agriculture and the production sector to services and crafts. All of the above changes can be deemed as positive as there is a gradual movement away from more vulnerable sectors. Accordingly, households that participate in livelihood activities related to agriculture and natural resource extraction are most affected by shocks and face the highest vulnerability to poverty. The paper additionally highlights some concerns such as a decline in availability of extracted products such as the fish stock which are expected to negatively impact on these more vulnerable rural households in the medium and longer term. Furthermore, the state of education is dismal and needs attention. Therefore, policy makers need to consider these issues while addressing rural poverty.
Keywords: Q57; Q20; Q12; 330; Livelihoods; Rural poverty; Diversification; Cluster Analysis; Cambodia